2012
DOI: 10.1029/2012pa002368
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic carbon and water masses during the Mystery Interval: A model‐data comparison study

Abstract: The ‘Mystery Interval’ (17.5–14.5 ka BP) is characterized by a large decline in atmospheric Δ14C synchronous with an increase in atmospheric CO2. The most widely accepted hypothesis to explain these observed shifts involves the existence of an isolated ‘old’ ocean carbon reservoir that was subsequently ventilated. Here we use the UVic Earth System Climate Model to locate a potential carbon rich and Δ14C depleted water mass under 17.5 ka BP boundary conditions. We then investigate two mechanisms for the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 94 publications
(184 reference statements)
4
25
0
1
Order By: Relevance
“…Menviel et al, 2014;Huiskamp and Meissner, 2012; see supplementary info) also show a Pacific-Atlantic seesaw, although this is most strongly expressed in the Northern Hemisphere. In these idealized model experiments, the North Atlantic is perturbed with freshwater, resulting in a cessation of NADW formation and decreased 14 C over most of the North Atlantic (including our study site) and below 2000 m in the South Atlantic (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Menviel et al, 2014;Huiskamp and Meissner, 2012; see supplementary info) also show a Pacific-Atlantic seesaw, although this is most strongly expressed in the Northern Hemisphere. In these idealized model experiments, the North Atlantic is perturbed with freshwater, resulting in a cessation of NADW formation and decreased 14 C over most of the North Atlantic (including our study site) and below 2000 m in the South Atlantic (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Mikolajewicz et al, 1997;Okazaki et al, 2010;Chikamoto et al, 2012;Huiskamp and Meissner, 2012) (Fig. 6).…”
Section: Resultsunclassified
“…A similar mechanism occurring during HS1 is also consistent with paleoproxy records as it lowers atmospheric δ 13 CO 2 [ Schmitt et al , ; Tschumi et al , ], decreases the ventilation age of deep Southern Ocean waters [ Skinner et al , ], and enhances mixing of Upper and Lower Circumpolar Deep Waters [ Burke and Robinson , ]. It is also consistent with a decrease in atmospheric Δ 14 C [ Huiskamp and Meissner , ; Matsumoto and Yokoyama , ]. Antarctic ice cores record an atmospheric CO 2 increase of 33 ppmv at the beginning of the last deglaciation and across HS1 [ Monnin et al , ].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies examined either the terrestrial carbon response [ Scholze et al , ; Köhler et al , ], the marine carbon cycle response [ Marchal et al , ; Chikamoto et al , ], or the combined marine and terrestrial carbon response [ Obata , ; Schmittner et al , ; Menviel et al , ; Schmittner and Galbraith , ; Bozbiyik et al , ; Bouttes et al , ; Huiskamp and Meissner , ; Matsumoto and Yokoyama , ] to an AMOC shutdown. While some modeling studies concluded that the oceanic carbon content increased as a result of an AMOC shutdown [ Obata , ; Menviel et al , ; Bozbiyik et al , ; Chikamoto et al , ], others suggested the opposite [ Marchal et al , ; Schmittner et al , ; Schmittner and Galbraith , ; Bouttes et al , ; Matsumoto and Yokoyama , ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, enhanced ocean remineralization length scales during the glacial, due to less active bacteria at low temperatures, could trap more DIC in the deep ocean, which then could account for additional CO 2 outgassing but would also reduce deep-ocean dissolved oxygen concentrations. Also the volume of isolated deep waters in the SO is uncertain; moreover, water masses in other oceans may also have contributed to the overall atmospheric pCO 2 change (Rose et al, 2010;Okazaki et al, 2010;Kwon et al, 2012;Huiskamp and Meissner, 2012). The T glob and pCO 2 changes after the MI across the BA, the Younger Dryas and the Holocene are not expected to be simulated in detail by the DCESS model.…”
Section: Discussion Of Transient Simulationsmentioning
confidence: 99%